Transfer of T6SSSPI-19from Salmonella Gallinarum to Salmonella Typhimurium Lacking T6SSSPI-6Complements its Colonization Defect in Mice - Pezoa Aros, David Antonio.; Blondel, Carlos J.; Amaya, Fernando A.; Santiviago, Carlos A. (Sciendo, 2023)
Salmonella genus harbors five Type VI Secretion System (T6SS) gene clusters. The T6SS encoded in SPI-6 (T6SSSPI-6) contributes to Salmonella Typhimurium colonization of chickens and mice, while the T6SS encoded in SPI-19 (T6SSSPI-19) of Salmonella Gallinarum contributes to chicken colonization. Interestingly, the T6SSSPI-19 of Salmonella Gallinarum complemented the defect in chicken colonization of a Salmonella Typhimurium strain that lacks the T6SSSPI-6, suggesting that both T6SSs are interchangeable. Here we show that the transfer of Salmonella Gallinarum T6SSSPI-19 complemented the defect in mice colonization of a Salmonella Typhimurium ΔT6SSSPI-6 strain, indicating that both T6SSs are functionally redundant during host colonization.
Keywords: SPI-19; T6SS; Colonización; Ratones; Salmonella typhimurium